2019
DOI: 10.1097/md.0000000000018331
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent changes in physical, mental, and quality of life outcomes in metoprolol-treated Chinese chronic heart failure patients

Abstract: This study assessed sex differences in cardiac and motor functions, quality of life (QoL), and mental status in Chinese chronic heart failure (CHF) patients after metoprolol treatment.This single-center prospective study, conducted from February 2013 to April 2016, included CHF patients (men and women) with resting heart rate (HR) >80 beats/min using metoprolol continuous release tablets. Metoprolol-induced changes in cardiac and motor functions, QoL, and mental status at 1, 3, 6, 9, and 12 months from baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…However, there have been concerns of psychiatric adverse events during β-blocker use [ 3 ], and sleep disturbances, psychoses, and depression are listed as potential adverse events in the summary of product characteristics for β-blockers [ 4 ]. This is supported by observational studies that found an increased risk of depression for patients using β-blockers [ 5 10 ]. Several case reports have linked β-blockers to psychosis and delirium but there are no larger studies on these outcomes.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…However, there have been concerns of psychiatric adverse events during β-blocker use [ 3 ], and sleep disturbances, psychoses, and depression are listed as potential adverse events in the summary of product characteristics for β-blockers [ 4 ]. This is supported by observational studies that found an increased risk of depression for patients using β-blockers [ 5 10 ]. Several case reports have linked β-blockers to psychosis and delirium but there are no larger studies on these outcomes.…”
Section: Introductionmentioning
confidence: 68%
“…Observational studies have also found an increased risk of suicide among individuals taking β-blockers as compared to controls [ 11 13 ]. However, there is contrasting evidence; β-blockers have been associated with decreases in depression and anxiety in other observational investigations [ 9 , 10 , 14 19 ] and a randomised controlled trial [ 20 ]. In addition, there are several observational studies [ 2 , 3 , 21 25 ] and randomised controlled trials [ 26 30 ] showing no associations with psychiatric events.…”
Section: Introductionmentioning
confidence: 99%
“…We assume that selective beta-blockers could not only improve energy metabolism and reduce hemodynamic alterations and proarrhythmogenic potential induced by excessive sympathetic excitation 311 but they might be more effective in alleviating mental stress and anxiety disorders. Indeed, selective beta-blockers decreased symptoms of anxiety in patients with chronic heart failure (metoprolol), 81 mitral valve prolapse syndrome (celiprolol) 70 and anxiety-related mental health problems (atenolol). 82 Prazosin, the alpha-1 antagonist, is currently used more often for indications other than hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The use of propranolol after experiencing 79 or recalling 80 traumatic events reduced the symptoms of anxiety and PTSD. Metoprolol lowered the anxiety score in chronic heart failure patients 81 and atenolol reduced PTSD and anxiety symptoms in patients with mental health problems 82 . There is even some evidence of an anxiolytic effect of beta‐blockers in healthy individuals 83 (Table 1).…”
Section: Cardiovascular Drugs and Anxietymentioning
confidence: 99%
“…Minnesota Living with Heart Failure Questionnaire (MLHFQ) is the most used instrument to evaluate the quality of life in patients with heart failure [ 9 11 ]. MLHFQ captures the symptom of HF and patients’ concerns, such as swelling, hospitalization, breathing, and so on.…”
Section: Introductionmentioning
confidence: 99%